2017
DOI: 10.1190/geo2016-0196.1
|View full text |Cite
|
Sign up to set email alerts
|

Model-based amplitude versus offset and azimuth inversion for estimating fracture parameters and fluid content

Abstract: The normal-to-shear fracture compliance ratio is commonly used as a fluid indicator. In the seismic frequency range, the fluid indicator lies between the values for isolated fluid-filled fractures and dry fractures, and it is not easy to discriminate the fluid content. Assuming that the fracture surfaces are smooth, we use [Formula: see text], with [Formula: see text] and [Formula: see text] representing the normal fracture weakness of the saturated and dry rock, to indicate fluid types, and to define a fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…The Gassmann fluid term and its product with mass density were used as a fluid discriminator by Russell et al (2003Russell et al ( , 2006, and Quakenbush et al (2006) used Poisson's ratio for the same purpose. Quintal (2012) suggested that frequency-dependent attenuation due to waveinduced fluid flow is a potential index of saturation, and Xue et al (2017) used a combination of the normal crack compliance of the saturated and dry rocks as a fluid factor.…”
Section: Introductionmentioning
confidence: 99%
“…The Gassmann fluid term and its product with mass density were used as a fluid discriminator by Russell et al (2003Russell et al ( , 2006, and Quakenbush et al (2006) used Poisson's ratio for the same purpose. Quintal (2012) suggested that frequency-dependent attenuation due to waveinduced fluid flow is a potential index of saturation, and Xue et al (2017) used a combination of the normal crack compliance of the saturated and dry rocks as a fluid factor.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic method is a valuable tool for the detection and characterization of fractures, due to the fact that seismic waves experience strong directional dependence, and are also significantly attenuated and delayed when propagating through fractures (Maultzsch et al 2003). For this reason, there is currently great interest in improving the understanding of seismic wave propagation through fractured rocks in general, and in presence of subvertical fractures in particular (Foord et al 2015;Xue et al 2017). Since seismic methods usually lack the resolution needed to directly image individual fractures, most efforts in this direction focus on exploiting the information encoded in the effective seismic properties of the probed fractured material.…”
Section: Introductionmentioning
confidence: 99%
“…AVAZ inversion is an ill condition; a large number of unknown parameters and the cross talk between the elastic and fracture parameters inevitably make several-term AVAZ inversion unstable (Downton et al 2006;Bachrach 2015). One tentative approach to reduce the number of unknown parameters is to implement azimuthal seismic amplitude difference inversion for fracture weakness estimation (Chen et al 2017a;Pan et al 2017;Xue et al 2017). In addition, Downton andRoure (2011, 2015) rewrote azimuthal P-wave reflectivity in terms of Fourier coefficients (FCs) and proposed an azimuthal Fourier coefficient elastic inversion for fracture parameters estimation.…”
Section: Introductionmentioning
confidence: 99%